METODOLOGIA PARA AVALIAÇÃO E CERTIFICAÇÃO DA SUSTENTABILIDADE DE EDIFICAÇÕES - ESTUDO DE CASO – IJUI/RS - Kolher, Raquel; Campos, Tâmela A.; Mensch, Natália G.; Scortegagna, Luiza A. U.; Strieder, Jaciele S. (Salão do Conhecimento, 2013)
Resumo